Preliminary research indicates that mechanical force through Pioze1 enhances local immunity during NPWT treatment for spinal infections - Xing, Hao; Pan, Junlin; Liu, Huan; Wang, Yanan; Chang, Zhengqi (Frontiers in Immunology, 2025)
ObjectiveThis study aims to investigate the mechanism by which Negative Pressure Wound Therapy (NPWT) regulates local immune responses in spinal infection through Piezo1-mediated mechanical stress, and elucidate its potential role in the treatment of spinal infections.MethodsFrom July 2021 to April 2022, a total of 7 patients with spinal infection treated with NPWT at our department were included in the study. The study analyzed clinical outcomes of spinal infection surgeries, including operative duration, intraoperative blood loss, postoperative drainage, improvements in pain levels as measured by the Visual Analogue Scale (VAS), and inflammatory markers such as C-reactive protein (CRP) and Erythrocyte Sedimentation Rate (ESR) measured one week before and after the procedure. Additionally, healing times and recurrence rates within two years post-surgery were assessed. In addition, lesion specimens were retained during surgery and changes in Piezo1, Interleukin-1β (IL-1β), IL-6, IL-8, and Tumor Necrosis Factor-α (TNF-α) in lesion tissues were observed before and after immunohistochemical analysis.ResultsAll 7 patients with spinal infections successfully underwent NPWT treatment and were ultimately cured. The average healing time was 45.71 ± 9.49 days, and there were no cases of recurrence or death during the two-year follow-up period. Surgical data showed a surgery duration of 96.57 ± 13.31 minutes, intraoperative blood loss of 65.71 ± 29.36 milliliters, and postoperative drainage of 163.57 ± 11.07 milliliters. Postoperatively, CRP, ESR, and VAS all significantly improved compared to preoperative levels (all p<0.05), which was superior to traditional treatment methods. Following NPWT intervention, the expression of Piezo1 protein at the lesion site significantly increased (0.03 ± 0.11 vs. 0.27 ± 0.22; p<0.05), while the expression levels of IL-1β, IL-6, IL-8, and TNF-α in the local immune microenvironment of the infected lesion significantly decreased (0.26 ± 0.11 vs. 0.16 ± 0.09, 0.27 ± 0.12 vs. 0.15 ± 0.67, 0.26 ± 0.18 vs. 0.10 ± 0.12, 0.35 ± 0.21 vs. 0.15 ± 0.11; p<0.05).ConclusionClinical results demonstrate that NPWT treatment for spinal infections exhibits remarkable efficacy, accompanied by a notable augmentation in local Piezo1 protein consistency. It is hypothesized that the mechanical force employed in NPWT treatment stimulates the Piezo1 protein, thereby modulating local immune cells and factors, ultimately bolstering local immunity. This study not only provides a molecular biology basis for a deeper understanding of the therapeutic effects of NPWT, but also offers new insights for optimizing treatment strategies for spinal infections.